On Lie Algebroids and Poisson Algebras - García-Beltrán, D.; Vallejo, J.A.; Vorobjev, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We introduce and study a class of Lie algebroids associated to faithful modules which is motivated by the notion of cotangent Lie algebroids of Poisson manifolds. We also give a classification of transitive Lie algebroids and describe Poisson algebras by using the notions of algebroid and Lie connections.